Attapulgite adsorbing material as well as preparation method and application thereof
The concave and convex rod is activated by ball milling, and its particle size and surface area are improved, which significantly enhances the adsorption ability to heavy metal ions, solves the problems of insufficient adsorption performance and high cost in the prior art, and achieves an efficient and low-cost heavy metal ions removal effect.
Patent Information
- Application Number
- CN202411707153.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-11-27
AI Technical Summary
The existing modified concave and convex rods have limited effects in improving the adsorption performance of heavy metal ions, and are costly and time-consuming, making it difficult to meet the needs of industrial production.
By controlling the ball milling speed, time and selecting matching grinding bead particle size, the particle size of the concave and convex rods is reduced, the specific surface area and the activation of the pores are increased, thereby improving its adsorption activity on heavy metal ions.
Compared with the raw ore, the removal rates of Pd2+ and Cd2+ by the ball mill activated concave and convex rod adsorbent materials have increased by 6 times and 4.5 times respectively. They are simple to operate and have low energy consumption, making them suitable for industrial production.
Smart Images

Figure CN119186486A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an adsorption material, in particular to an attapulgite adsorption material, and also to the application of the attapulgite adsorption material in adsorbing heavy metal ions, belonging to the technical field of heavy metal water pollution treatment. Background Art
[0002] The global water pollution problem has reached a very serious level. Due to the insufficient water resources, there is little fresh water left to be used, so it is urgent to control water pollution. Among various water pollutants, heavy metal ions are often the most threatening. Therefore, in order to improve and maintain water quality, the excessive heavy metals in water must be effectively controlled. At present, there are many processes for treating water pollutants, such as chemical precipitation, electrochemical degradation, membrane permeation, coagulation, and biodegradation. Among them, the adsorption method has broad development prospects due to its simple operation, low cost and high efficiency.
[0003] Attapulgite, also known as palygorskite, is a 2:1 chain-shaped magnesium aluminum silicate mineral. Attapulgite has the characteristics of large specific surface area, many pores, rich surface hydroxyl groups, high catalytic site activity and non-toxicity, and is widely used in adsorption, catalysis, medicine and food fields. Natural attapulgite ore has defects such as many associated ores, rod crystal aggregation and large particle size, resulting in low overall adsorption performance.
[0004] At present, there are many methods for modifying attapulgite to improve its adsorption performance for heavy metal ions. For example, the Chinese patent (publication number: CN117482930 A) specifically discloses that attapulgite is refined and modified to obtain refined modified attapulgite; the refined modified attapulgite is calcined in an air atmosphere to obtain an attapulgite adsorbent that quickly adsorbs and removes heavy metal ions. This method can improve the adsorption rate and adsorption selectivity of heavy metals by modifying attapulgite. The method for modifying attapulgite requires a high-temperature calcination process, which has high energy consumption and high cost. A Chinese patent (publication number: CN104528863B) discloses that attapulgite is modified by reacting a surfactant such as cationic gemini, 0.5-2 mol / L hydrochloric acid and deionized water at a temperature of 50-65°C and a rotation speed of 100-250 rpm for 2.5-5 hours. The modified attapulgite has a 30% higher removal efficiency of heavy metals in landfill leachate than the unmodified attapulgite. However, this method does not significantly improve the adsorption performance of attapulgite. Summary of the invention
[0005] In view of the technical problems that the existing methods for modifying attapulgite have limited ability to improve the adsorption performance of attapulgite ore, high cost, long time consumption, etc., the first object of the present invention is to provide a method for modifying Pd in aqueous solution. 2+ 、Cd 2+The attapulgite adsorption material has high adsorption activity for heavy metal ions such as Pd 2+ 、Cd 2+ The adsorption effect of 2-hydroxy-1-nitropropene was increased by about 6 times and 4.5 times respectively.
[0006] The second object of the present invention is to provide a method for preparing a attapulgite adsorption material with high heavy metal ion adsorption activity using attapulgite ore. This method uses a simple one-step ball milling activation to achieve the reduction of the attapulgite particle size and the activation of the adsorption channels, thereby greatly improving the adsorption activity of the attapulgite for heavy metal ions. This method is simple to operate, has low energy consumption, and is conducive to industrial production.
[0007] The third object of the present invention is to provide an application of a attapulgite adsorption material, which is used for the adsorption of heavy metal ions in an aqueous solution system. It has the characteristics of large adsorption capacity and fast adsorption rate. Compared with the attapulgite ore, its adsorption activity for heavy metal ions is greatly improved.
[0008] In order to achieve the above technical objectives, the present invention provides a method for preparing a attapulgite adsorption material, which comprises crushing and ball milling the attapulgite ore to obtain the attapulgite adsorption material; the ball milling conditions are as follows: the ball milling speed is 600-700 rad / min, and the ball milling time is 10-60 min; three types of grinding beads with particle sizes of 4-6 mm, 9-11 mm and 14-16 mm are used in the ball milling process, and the mass ratio of the three types of grinding beads is 3-5: 3-5:1.
[0009] The present invention activates the attapulgite ore by ball milling. By controlling the ball milling speed, time and selecting matching grinding beads, the adsorption channels of the attapulgite can be activated while reducing the particle size of the attapulgite and increasing its specific surface area, thereby greatly improving the adsorption activity of the attapulgite to heavy metal ions. More specifically, ball milling activation mainly changes the original physical and chemical properties of the attapulgite through mechanical force, so that it exhibits more excellent physical and chemical properties. Under the action of mechanical force, the grinding medium and the attapulgite produce disordered collisions, and the force generated by the collision exceeds the mechanical load that the attapulgite can withstand, which is manifested in the macroscopic reduction of the particle size of the attapulgite and a significant increase in the specific surface area, and in the microscopic manifestation of the generation of lattice defects, the exposure of adsorption active sites, and the change of surface potential. The ball milling speed and time and the matching of the ball milling medium and the particle size of the attapulgite ore have a great influence on the activation of the attapulgite. Grinding beads of different particle sizes have different abilities to act on attapulgite. For example, grinding beads with large particle sizes mainly act on large-particle attapulgite minerals, but have little effect on small-particle attapulgite particle minerals. Selecting grinding beads of different particle sizes to activate attapulgite can make the attapulgite activated more evenly. The ball milling speed and ball milling time are also very important operating parameters. Under appropriate ball milling parameters, the adsorption active sites of attapulgite can be stimulated to the greatest extent, the particle size can be reduced, and the specific surface area can be increased. If the ball milling activation is excessive, it will lead to the aggregation of attapulgite particles, reduce the specific surface area, and weaken its adsorption activity.
[0010] As a preferred solution, the ball milling time is 40 to 60 minutes or the ball milling time is 20 to 40 minutes. Under the premise of the ball milling speed and the selected grinding beads, when the ball milling time is 40 to 60 minutes, the obtained attapulgite adsorption material has the best adsorption effect on cadmium ions, and when the ball milling time is 20 to 40 minutes, the obtained attapulgite adsorption material has the best adsorption effect on lead ions.
[0011] As a preferred solution, the shape of the grinding beads is spherical and / or cylindrical. The shape of the grinding beads is further preferably cylindrical. The contact modes of spherical and cylindrical grinding beads with attapulgite are different. The spherical one is mainly point contact, while the cylindrical one has point contact, line contact and surface contact. Therefore, the cylindrical grinding beads are used to ball-mill and activate the attapulgite. Compared with the spherical medium, there are three more contact modes, namely point-line contact, line-line contact and surface-surface contact. The point contact of the spherical grinding beads has a relatively small effective area, so the force is the largest, which may cause uneven grinding of attapulgite particles, and there is a phenomenon that the particles are ground too finely and the rod crystals are destroyed. The line contact and surface contact of the cylindrical medium can well alleviate the problem that the force between the spherical grinding beads and the attapulgite is large and destroys the microstructure of the attapulgite. There are three ways of contact between the cylindrical grinding beads and the attapulgite, namely point-point contact, line-line contact and surface-surface contact. Whether it is the contact area or the collision force, it is richer and more diverse than that of the spherical grinding beads. Therefore, whether it is large, medium or small attapulgite mineral particles, cylindrical grinding beads can have corresponding action modes to crush and activate them; while spherical grinding beads are too monotonous, mainly acting on large particles, and medium and small particles may not be fully ground and activated due to the low contact probability. Therefore, the preferred grinding beads are cylindrical grinding beads.
[0012] As a preferred solution, the filling amount of the grinding beads in the ball mill is 0.9-1.0 kg / L.
[0013] As a preferred solution, the ball milling is wet ball milling.
[0014] As a preferred solution, the wet ball milling uses water as the ball milling solvent.
[0015] As a preferred solution, the ball milling solvent and the attapulgite ore are added in a solid-to-liquid ratio of 0.1 to 0.2 g / mL.
[0016] As a preferred solution, a dispersant with a mass concentration of 4% to 5% is added during the ball milling process. The dispersant is specifically sodium hexametaphosphate.
[0017] As a preferred solution, three types of grinding beads with particle sizes of 5 mm, 10 mm and 15 mm are further preferably used in the ball milling process. The mass ratio of the three types of grinding beads (from small to large) in the ball milling process is further preferably 3-4: 4-5: 1. The material of the grinding beads is zirconium oxide.
[0018] The attapulgite ore of the present invention is crushed to a particle size of less than 2 mm.
[0019] The ball milled material of the present invention is dried at a temperature of 60°C.
[0020] The invention also provides a attapulgite adsorption material, which is obtained by the preparation method.
[0021] The invention also provides an application of the attapulgite adsorption material, which is used for adsorbing heavy metal ions in an aqueous solution.
[0022] As a preferred embodiment, the heavy metal ions include Pd 2+ and / or Cd 2+ .
[0023] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:
[0024] (1) The present invention adopts mechanical activation to effectively improve the adsorption performance of attapulgite ore. Compared with attapulgite ore, the attapulgite adsorption material prepared by mechanical activation has a better adsorption performance on Pd 2+ 、Cd 2+ The removal rates increased by nearly 6 times and 4.5 times respectively.
[0025] (2) The method for preparing the attapulgite adsorption material adopted in the present invention is simple and convenient, which greatly reduces the cost and simplifies the operation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the particle size distribution diagram of the attapulgite ore in Example 1 after grinding for 10 to 60 min.
[0027] Figure 2 The Pd content of the attapulgite ore at different grinding times in Example 1 2+ Removal rate enhancement ratio diagram.
[0028] Figure 3 This is the particle size distribution diagram of the attapulgite ore in Example 2 after grinding for 10 to 60 min.
[0029] Figure 4 The Cd content of the attapulgite ore at different grinding times in Example 2 2+ Removal rate enhancement ratio diagram.
[0030] Figure 5 The Pd 2+ and Cd 2+ Removal rate enhancement ratio diagram.
[0031] Figure 6 The results of the comparison of the attapulgite ore with different particle size grinding beads ratios on Pd 2+ and Cd 2+ Removal rate enhancement ratio diagram. DETAILED DESCRIPTION
[0032] The content of the present invention is further described in detail below in conjunction with specific embodiments, but the following specific embodiments do not limit the protection scope of the claims of the present invention.
[0033] Example 1
[0034] (1) Crushing the ore: The attapulgite ore of the present invention comes from Xuyi, Jiangsu. The blocky attapulgite is simply picked to remove the obvious miscellaneous ores, and the remaining ores are mechanically crushed to less than 2 mm.
[0035] (2) Grinding of attapulgite: The grinding test was carried out in a zirconia jar with an internal volume of 100 mL. The material of the grinding ball media is zirconia, the shape of the grinding ball media is cylindrical, and the sizes of the grinding ball media are 15 mm, 10 mm and 5 mm. The filling amount of the grinding ball media in the experiment was 100 g. The grinding method was wet grinding, the solid-liquid ratio was 1:5 (5 g of attapulgite ore corresponds to 25 mL of ultrapure water), the amount of dispersant was 4% (0.2 g of sodium hexametaphosphate), the speed of the planetary ball mill was 700 rad / min, the grinding ball media size ratio (large: medium: small = 1:5:3), and the grinding time was 10, 20, 30, 40, 50 and 60 min respectively. The particle size distribution of attapulgite minerals under different ball milling times is shown in the figure. Figure 1 As shown, the attapulgite adsorption materials obtained at different ball milling times were respectively recorded as attapulgite A-10, attapulgite A-20, attapulgite A-30, attapulgite A-40, attapulgite A-50 and attapulgite A-60.
[0036] (3) Drying the attapulgite: The ground slurry is dried in an air atmosphere at 60°C until the water is evaporated.
[0037] (4) Pd adsorption 2+ :Measure 50 mL of 20 mg / L Pd 2+ The solution was placed in a conical flask, with a total of 6 portions as controls, and 50 mg of attapulgite A-10, attapulgite A-20, attapulgite A-30, attapulgite A-40, attapulgite A-50 and attapulgite A-60 were added respectively. The solution system was run at 25 ° C and 200 rpm for 4 h. After the adsorption reaction was completed, the supernatant was filtered and tested to calculate the Pd 2+ The results show that the removal rate of Pd 2+ It showed good adsorption and the removal rate increased by nearly 6 times year-on-year. The specific data are as follows Figure 2 shown.
[0038] Example 2
[0039] (1) Crushing the ore: See Example 1.
[0040] (2) Grinding of attapulgite: The grinding test was carried out in a zirconia jar with an internal volume of 100 mL. The material of the grinding ball medium is zirconia, the shape of the grinding ball medium is round, and the sizes of the grinding ball medium are 15 mm, 10 mm and 5 mm. The filling amount of the grinding ball medium in the experiment is 100 g. The grinding method is wet grinding, the solid-liquid ratio is 1:5 (5 g of attapulgite ore corresponds to 25 mL of ultrapure water), the amount of dispersant is 4% (0.2 g of sodium hexametaphosphate), and the speed of the planetary ball mill is 700 rad / min. The grinding ball medium size ratio (large: medium: small = 1:3:5) and the grinding time are 10, 20, 30, 40, 50, and 60 min, respectively. The particle size distribution of attapulgite minerals under different ball milling times is shown in the figure. Figure 3 As shown, the attapulgite adsorption materials obtained at different ball milling times were respectively recorded as attapulgite B-10, attapulgite B-20, attapulgite B-30, attapulgite B-40, attapulgite B-50 and attapulgite B-60.
[0041] (3) Drying the attapulgite: The ground slurry is dried in an air atmosphere at 60°C until the water is evaporated.
[0042] (4) Adsorption of Cd 2+ :Measure 50 mL of 20 mg / L Cd 2+ The solution was placed in a conical flask, with a total of 6 portions as controls, and 50 mg of attapulgite B-10, attapulgite B-20, attapulgite B-30, attapulgite B-40, attapulgite B-50 and attapulgite B-60 were added respectively. The solution system was run at 25°C and 200 rpm for 4 h. After the adsorption reaction was completed, the supernatant was filtered and tested to calculate Cd 2+ The results show that the removal rate of Cd by attapulgite B-60 2+ It showed good adsorption, and the removal rate increased by nearly 4.5 times year-on-year. The specific data are as follows Figure 4 shown.
[0043] Others are the same as in Example 1
[0044] Comparative Example 1
[0045] Take 50 mg of attapulgite ore and add 50 mL of 20 mg / L Pd 2+ and Cd 2+ The system was run at 25°C and 200 rpm for 4 h. After the adsorption reaction was completed, the supernatant was filtered and tested to calculate the Pd 2+ and Cd 2+ The results show that the removal rate of Pd 2+ and Cd 2+ The adsorption capacity is very poor, and the removal rate is about 10%.
[0046] Example 3
[0047] (1) Crushing the ore: See Example 1.
[0048] (2) Grinding of attapulgite: The grinding test was carried out in a zirconia jar with an internal volume of 100 mL. The material of the grinding ball media was zirconia, and the shapes of the grinding ball media were cylindrical and spherical. As a control, the grinding ball media had three sizes of 15 mm, 10 mm and 5 mm. The filling amount of the grinding ball media in the experiment was 100 g. The grinding method was wet grinding, the solid-liquid ratio was 1:5 (5 g of attapulgite ore corresponds to 25 mL of ultrapure water), the amount of dispersant was 4% (0.2 g of sodium hexametaphosphate), and the speed of the planetary ball mill was 700 rad / min. The grinding ball media size ratio (large: medium: small = 1:5:3) and the grinding time were 30 min. The obtained attapulgite adsorption materials were recorded as attapulgite C1-30 and attapulgite C2-30.
[0049] (3) Drying the attapulgite: The ground slurry is dried in an air atmosphere at 60°C until the water is evaporated.
[0050] (4) Pd adsorption 2+ and Cd 2+ : Take 50 mL of 20 mg / L Pd 2+ and Cd 2+ The solution was placed in a conical flask, and 50 mg of attapulgite C1-30 and attapulgite C2-30 were added respectively. The solution system was run at 25°C and 200 rpm for 4 h. After the adsorption reaction was completed, the supernatant was filtered and tested to calculate the Pd 2+ and Cd 2+ The results show that the attapulgite C1-30 obtained by the cylindrical medium activation treatment has a significant effect on the removal rate of Pd 2+ and Cd 2+ It shows good adsorption, and the effect is better than that of attapulgite C2-30. The specific data are as follows Figure 4 shown.
[0051] Example 4
[0052] (1) Crushing the ore: See Example 1.
[0053] (2) Grinding of attapulgite: The grinding test was carried out in a zirconia jar with an internal volume of 100 mL. The grinding ball medium was made of zirconia, the grinding ball medium was cylindrical, and the grinding ball medium sizes were 15 mm, 10 mm, and 5 mm. The filling amount of the grinding ball medium in the test was 100 g. The grinding method was wet grinding, the solid-liquid ratio was 1:5 (5 g of attapulgite ore corresponds to 25 mL of ultrapure water), the amount of dispersant was 4% (0.2 g of sodium hexametaphosphate), and the speed of the planetary ball mill was 700 rad / min. Three groups of grinding ball medium size ratios were used as controls, namely: large: medium: small = 1:5:3, 1:4:4, 1:3:5, and the grinding time was 30 min. The obtained attapulgite adsorption materials were recorded as attapulgite D-153, attapulgite D-144, and attapulgite D-135, respectively.
[0054] (3) Drying the attapulgite: The ground slurry is dried in an air atmosphere at 60°C until the water is evaporated.
[0055] (4) Pd adsorption 2+ and Cd 2+ : Take 50 mL of 20 mg / L Pd 2+ and Cd 2+ The solution was placed in a conical flask, and 50 mg of attapulgite D-153, attapulgite D-144, and attapulgite D-135 were added respectively. The solution system was run at 25 °C and 200 rpm for 4 h. After the adsorption reaction was completed, the supernatant was filtered and tested to calculate the Pd 2+ and Cd 2+ The results show that attapulgite D-153 and attapulgite D-135, respectively, have a 2+ and Cd 2+ showed the best adsorption, while attapulgite D-144 had the best adsorption for Pd 2+ and Cd 2+ All of them show moderate adsorption performance. This is mainly based on the fact that the hydrated ion radius of lead ions is larger, and they are more inclined to complete adsorption on the surface of attapulgite. The hydroxyl and siloxy groups on the surface of attapulgite can combine with lead ions. D-153 contains less small-particle grinding media, which can avoid the destruction of the adsorption groups on the surface of attapulgite by the grinding media. Therefore, with the increase of small-particle grinding media, the destruction of the adsorption groups on the surface of attapulgite is more obvious, resulting in a decrease in the removal rate of lead ions. The hydrated ion radius of cadmium ions is smaller, and they are mainly adsorbed in the pores of attapulgite. Small-sized grinding media can grind the attapulgite more finely and optimize the pore size and pore volume of the attapulgite. Therefore, the performance of D-135 in removing cadmium ions will be better than that of D-153 and D-144. Specific data are as follows Figure 6 shown.
Claims
1. A method for preparing a attapulgite adsorption material, characterized in that: The attapulgite raw ore is crushed and ball-milled to obtain the attapulgite adsorption material; The ball milling conditions are as follows: the ball milling speed is 600-700 rad / min, and the ball milling time is 10-60 min; In the ball milling process, three types of grinding beads with particle sizes of 4-6 mm, 9-11 mm and 14-16 mm are used, and the mass ratio of the three types of grinding beads is 3-5: 3-5:
1.
2. The method for preparing a attapulgite adsorption material according to claim 1, characterized in that: The grinding beads are spherical and / or cylindrical in shape.
3. The method for preparing a attapulgite adsorption material according to claim 2, characterized in that: The filling amount of the grinding beads in the ball mill is 0.9-1.0 kg / L.
4. The method for preparing a attapulgite adsorption material according to claim 1 or 2, characterized in that: The ball milling is wet ball milling; The wet ball milling uses water as the ball milling solvent; The ball milling solvent and the attapulgite ore are added according to a solid-liquid ratio of 0.1 to 0.2 g / mL.
5. The method for preparing a attapulgite adsorption material according to claim 4, characterized in that: A dispersant with a mass concentration of 4% to 5% is added during the ball milling process.
6. A attapulgite adsorption material, characterized in that: Obtained by the preparation method according to any one of claims 1 to 5.
7. The use of the attapulgite adsorption material according to claim 6, characterized in that: Used to adsorb heavy metal ions in aqueous solutions.
8. The use of the attapulgite adsorption material according to claim 7, characterized in that: The heavy metal ions include Pd 2+ and / or Cd 2+ .
Citation Information
Patent Citations
Particulate attapulgite adsorbent and preparation method thereof
CN104014299A
Amorphous carbon composite metal oxide Yolk-Shell material and preparation method and application thereof
CN115140727A
Preparation method and application of sepiolite material based on mechanical activation
CN117504809A
